The Relationship of Quality and Quantity of Post-Secondary Agricultural Mechanics Training of School-Based Agricultural Education Teachers - Gent, Nichole; Anderson, Ryan; Paulsen, Thomas (Journal of Agricultural Systems, Technology, and Management, 2024)
Agricultural mechanics coursework has historically been considered an important component of the school-based agricultural education (SBAE) curriculum (Burris, et al., 2005). Agricultural mechanics courses have been a foundational piece of agricultural programs since 1917 when agriculture emerged as a part of the public education system (National FFA Organization, 2014). Evidence has indicated SBAE teachers feel less comfortable teaching agricultural mechanics courses than any other agricultural-related content area (Burris, et al., 2010). The purpose of this study was to determine if a relationship existed between the perceived quality and quantity of agricultural mechanics training that SBAE teachers received during the preservice teacher training programs. A researcher-modified, paper-based questionnaire addressed the objective of the study. Based on our findings, we conclude a strong positive correlation exists between the perceived amount (quantity) of training and the quality of training that secondary SBAE teachers received at the post-secondary level. Efforts should be made at the post-secondary level to expand the agricultural mechanics coursework and offerings for preservice agricultural education teachers. Teacher education programs should continue to develop high quality agricultural mechanics coursework consistent with practitioners' needs. Further research should be conducted to determine if SBAE teachers who were required to complete several agricultural mechanics courses have the same perception of quality of training at the post-secondary level to determine if other factors affect their comfort of teaching agricultural mechanics courses.